Co-Registration of Peripheral Atherosclerotic Plaques Assessed by Conventional CT Angiography, MicroCT and Histology in Patients with Chronic Limb Threatening Ischaemia. (January 2021) - Kuntz, Salomé H.; Jinnouchi, Hiroyuki; Kutyna, Matthew; Torii, Sho; Cornelissen, Anne; Sakamoto, Atsushi; Sato, Yu; Fuller, Daniela T.; Schwein, Adeline; Ohana, Mickael; Gangloff, Hugo; Lejay, Anne; et al.
Abstract : Objective: To co-register conventional computed tomography angiography (CTA), with ex vivo micro-computed tomography (microCT) and histology of popliteal atherosclerotic plaques. Improving the non-invasive imaging capabilities may be valuable to advance patient care with peripheral arterial obstructive disease towards lesion and individual based treatment. Methods: In this prospective observational study, 12 popliteal arteries from 11 symptomatic patients who had undergone transfemoral amputations for chronic limb threatening ischaemia and who had pre-operative CTA, were analysed ex vivo by microCT and histology. A total of 353 histological cross sections were co-registered with microCT and CTA, and classified as: lipid rich (LP, n = 26), fibrous (FP, n = 80), or calcific (CP, n = 247) plaques. CTA and microCT plaque density was calculated in 791 regions of interest as Hounsfield units (HU). Results: CTA and microCT could identify plaque components that were confirmed by histology such as fibrous tissue (FP), lipid pool/core (LP), and calcification (CP). MicroCT densities were 77.8 HU for FP (IQR 52.8, 129.5 HU), −28.4 HU for LP (IQR −87.1, 13.2 HU), and 3826.0 HU for CP (IQR 2989.0, 4501.0 HU). CTA densities of the three components of the plaque were: 78.0 HU for FP (IQR 59.5, 119.8 HU), 32.5 HU for LP (IQR 15.0, 42 HU), and 641.5 HU for CP (IQR 425.8, 1135 HU). The differences were statistically significant between the HU densitometric characteristics among the three groups ( p < .0001) for both imaging modalities. Overall, microCT performed better diagnostically than conventional CTA for the three types of plaques: areas under the receiving operator characteristics curve were greater for microCT than CTA for FP (0.97 vs. 0.90), for LP (0.88 vs. 0.67), and for CP (0.97 vs. 0.90). Conclusion: CTA and microCT can be used to identify histological atherosclerotic plaque components, with better diagnostic performance for microCT. This study demonstrates the feasibility of using microCT to assess plaque morphology lesions in a manner that approaches histology thus becoming a useful tool for ex vivo assessment of atherosclerosis and towards lesion based treatment.